Emergence of a new disease as a result of interspecific virulence gene transfer - Friesen, T.; Stukenbrock, E.; Liu, Z.; Meinhardtb, S.; Ling, H.; Faris, J.; Rasmussen, J.; Solomon, P.; McDonald, B.; Oliver, Richard (Nature Publishing Group, 2006)
New diseases of humans, animals and plants emerge regularly. Enhanced virulence on a new host can be facilitated by the acquisition of novel virulence factors. Interspecific gene transfer is known to be a source of such virulence factors in bacterial pathogens (often manifested as pathogenicity islands in the recipient organism(1)) and it has been speculated that interspecific transfer of virulence factors may occur in fungal pathogens(2). Until now, no direct support has been available for this hypothesis. Here we present evidence that a gene encoding a critical virulence factor was transferred from one species of fungal pathogen to another. This gene transfer probably occurred just before 1941, creating a pathogen population with significantly enhanced virulence and leading to the emergence of a new damaging disease of wheat.